The impact of information accuracy on the selective trust of children aged 3–6 - Shu Mou; Xiu Mu; Nan Wu; Yifang Wang (Frontiers in Psychology)
Promoting young children’s selective trust ability and interpersonal safety knowledge is the goal of many child educational administrations and maltreatment prevention programs, but questions remain about the factors that influence the development and effectiveness of these skills. The goal of this study was to explore the impact of information accuracy on selective trust in children aged 3–6 years as well as the roles of informant gender and safety knowledge. Using a real-world contextual experimental paradigm, we conducted two experiments using a 2 (age group: 3–4 years vs. 5–6 years) × 2 (information accuracy: accurate vs. inaccurate) between-subjects design to examine whether children would follow a female/male stranger when confronted with accurate/inaccurate information and to measure the length of time the children hesitated when making the decision to leave. The role of safety knowledge in the decision process was also tested by questionnaire. We found that: (1) information accuracy significantly influenced selective trust among 5–6-year-olds; (2) regardless of whether the information was accurate or not, children aged 5–6 years hesitated longer than children aged 3–4 years in choosing to leave; (3) more 3–6-year-olds chose to trust a female stranger than a male stranger; and (4) 5–6 year-old children’s safety knowledge about prevention of abduction has a protective role in selective trust.